Managing the endogeneity problem of the market structure: a study on banking competition - Tri Mulyaningsih; Anne Daly; Riyana Miranti (Economic Journal of Emerging Markets, 2015)
Recent literature suggests that the market structure is an endogenous variable that is determined by a firm’s behaviour and the competitive environment of the industry. This study examines the relation between the market structure and the banks’ behaviour in Indonesian banking by considering the endogeneity problem of them as variables. The estimations using the Vector-Error-Correction approach suggest that the structural approach provides a valid prediction of the relationship between market structure and bank behaviour by recognizing the endogeneity issue between those two variables. The banking industry would be more competitive if the market was less concentrated.